2018
DOI: 10.1186/s12864-018-4770-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences between fast and slow muscles in scallops revealed through proteomics and transcriptomics

Abstract: BackgroundScallops possess striated and catch adductor muscles, which have different structure and contractile properties. The striated muscle contracts very quickly for swimming, whereas the smooth catch muscle can keep the shells closed for long periods with little expenditure of energy. In this study, we performed proteomic and transcriptomic analyses of differences between the striated (fast) and catch (slow) adductor muscles in Yesso scallop Patinopecten yessoensis.ResultsTranscriptomic analysis reveals 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 79 publications
3
13
0
Order By: Relevance
“…In this study, we noted an inconsistency in the expression between mRNA and protein levels of MyHC isoforms in the fetal vastus and kid ST muscles. Similar differences in mRNA and protein abundances of MyHC genes have been reported in other species [35]. Generally, the protein accretion rate of hindlimb muscle is approximately 0.17% per day in ovine fetuses [36] and 0.8% in young lambs [37].…”
Section: Discussionsupporting
confidence: 78%
“…In this study, we noted an inconsistency in the expression between mRNA and protein levels of MyHC isoforms in the fetal vastus and kid ST muscles. Similar differences in mRNA and protein abundances of MyHC genes have been reported in other species [35]. Generally, the protein accretion rate of hindlimb muscle is approximately 0.17% per day in ovine fetuses [36] and 0.8% in young lambs [37].…”
Section: Discussionsupporting
confidence: 78%
“…The Pifuc-TnC gene is predominantly expressed in phasic muscle, which leads us to suggest that Pifuc-TnC is involved in phasic muscle contraction. Our prediction is also supported by a recent comprehensive survey of gene expression patterns in scallop adductor muscle using proteomic and transcriptomic analyses that showed that the genes of all the troponin subunits are more highly expressed in phasic muscle compared with catch muscle [10]. However, to evaluate our prediction, elucidation of the function(s) of Tn in molluscan phasic muscle is required.…”
Section: Introductionsupporting
confidence: 73%
“…The P. yessoensis β-actin gene was used as an internal reference [6, 46]. The comparative Ct method (2 -△△Ct method) was used to calculate the relative gene expressions of the samples, which were normalized using the β-actin mRNA level.…”
Section: Methodsmentioning
confidence: 99%